Evaluation of the Questions in Geography Textbook to Promote Higher Order Thinking - Ahyuni, Ahyuni; Purwaningsih, Endah; Nur, Hamdi; Aziz, Azwirda (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
Geography investigates issues and topics of the environment and people by using the spatial perspective. It requires the concept of space, using tools of representation and engaging a higher cognitive process. Therefore, it is necessary to evaluate the cognitive level of the questions in geography textbooks, especially that of spatial thinking. Evaluation of spatial thinking is not sufficiently referring to Bloom's taxonomy because it does not identify the using tools of representation and various levels of spatial concepts as an important part of reasoning. This research addresses by examining the distribution of questions in geography book for Senior High School in Indonesia by using both Bloom's and spatial thinking taxonomy. It was found that the questions were mostly at the lower level of thinking, which seems more intended just to recall and retrieval the information. It was also found that there are very few questions that belong to spatial thinking.